Turning back the tide of American mink invasion at unprecedented scales in partnership with communities - Lambin, X. (Julius-Kühn-Archiv, 2011)
Successful eradications of harmful invasive species have been mostly confined to islands while control programs in mainland areas remain small, uncoordinated and vulnerable to recolonisation. We took an adaptive approach to achieve large scale eradication of invasive American mink in a mainland area in North East Scotland. Capitalising on the convergent interests of a diverse range of local stakeholders, we created a coordinated coalition of trained volunteers to detect and trap mink. Starting in montane headwaters, we systematically moved down river catchments, deploying mink rafts, an effective detection and trapping platform. Volunteers took increasing responsibility for raft monitoring and mink trapping as the project progressed. Within 3 years, all breeding mink had been removed from 10,570 km² with the involvement of 186 volunteers. Capture rate within sub-catchments increased with connectivity to mink in other sub-catchments and with proximity to the coast where there is more productive habitat. The main factor underpinning the success of this project was functional volunteer participation.